Imaging Plant Lipids with Fluorescent Reporters - Yong-Kang Li; Guang-Yi Dai; Yu-Meng Zhang; Nan Yao (Plants)
In plants, lipids function as structural elements and signaling molecules. Understanding lipid composition and dynamics is essential for unraveling their biological functions and metabolism. Mapping the spatiotemporal distribution of lipids in plants holds great potential for elucidating lipid biosynthetic pathways and gaining insights to guide crop genetic engineering. Recent progress in fluorescence microscopy and imaging has opened new opportunities for researchers to visualize plant lipids in vivo at high spatiotemporal resolution. In this review, we provide an up-to-date overview of the methods used to image plant lipids with fluorescence microscopy. We highlight caveats and potential limitations of these approaches and provide suggestions for optimizing their utilization. This review synthesizes current knowledge and highlights the potential of these methods to provide new insights into lipid biology.